Agriculture, food security and climate change: Outlook for knowledge, tools and action - Vermeulen, Sonja J.; Aggarwal, Pramod K.; Ainslie, A.; Angelone, C.; Campbell, Bruce M.; Challinor, Andrew J.; Hansen, James; Ingram, John S.I.; Jarvis, Andy; Kristjanson, Patricia M.; Lau, Charlotte; Thornton, Philip K.; et al. (CGIAR-ESSP Program on Climate Change, Agriculture and Food Security, 2010)
Agriculture and food security are key sectors for intervention under climate change. Agricultural production is highly vulnerable even to 2C (lowend) predictions for global mean temperatures in 2100, with major implications for rural poverty and for both rural and urban food security. Agriculture also presents untapped opportunities for mitigation, given the large land area under crops and rangeland, and the additional mitigation potential of aquaculture. This paper presents a summary of current scientific knowledge on the impacts of climate change on farming and food systems, and on the implications for adaptation and mitigation. Many of the trends and impacts are highly uncertain at a range of spatial and temporal scales; we need significant advances in predicting how climate variability and change will affect future food security. Despite these uncertainties, it is clear that the magnitude and rate of projected changes will require adaptation. Actions towards adaptation fall into two broad overlapping areas: (1) better management of agricultural risks associated with increasing climate variability and extreme events, for example improved climate information services and safety nets, and (2) accelerated adaptation to progressive climate change over decadal time scales, for example integrated packages of technology, agronomy and policy options for farmers and food systems. Maximization of agriculture’s mitigation potential will require, among others, investments in technological innovation and agricultural intensification linked to increased efficiency of inputs, and creation of incentives and monitoring systems that are inclusive of smallholder farmers. The challenges posed by climate change to agriculture and food security require a holistic and strategic approach to linking knowledge with action. Key elements of this are greater interactions between decision-makers and researchers in all sectors, greater collaboration among climate, agriculture and food security communities, and consideration of interdependencies across whole food systems and landscapes. Food systems faced with climate change need urgent action in spite of uncertainties.